2014
DOI: 10.1016/j.hrtlng.2013.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility and inter-rater reliability of the ICU Mobility Scale

Abstract: The IMS is a feasible tool with strong inter-rater reliability for measuring the maximum level of mobility of adult patients in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
234
0
29

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(294 citation statements)
references
References 26 publications
1
234
0
29
Order By: Relevance
“…The patient could receive assistance from staff or equipment but the patient actively participated in the exercise at the highest functional level. [15] The goal of EGDM was to maximise safe physical activity (Figure 1). [15] A physical therapy mobility team led EGDM.…”
Section: Intervention -Early Goal-directed Mobility (Egdm)mentioning
confidence: 99%
“…The patient could receive assistance from staff or equipment but the patient actively participated in the exercise at the highest functional level. [15] The goal of EGDM was to maximise safe physical activity (Figure 1). [15] A physical therapy mobility team led EGDM.…”
Section: Intervention -Early Goal-directed Mobility (Egdm)mentioning
confidence: 99%
“…Un estudio no reportó el tamaño muestral según sexo 38,39 . En 2 estudios se describió la edad de la muestra, cuyos promedios fueron entre 51,0 y 64,5 años [40][41][42][43] (Tabla 1). De las patologías de ingreso a UPC, especificadas, las principales fueron quirúrgicas (46,0%), seguidas por enfermedades respiratorias (17,5%) (Tabla 2).…”
Section: Características De Los Estudios Primariosunclassified
“…Both the ACIF (ICC 0.94) and IMS (ICC 0.8) (Hodgson et al, 2014) have acceptable interrater reliability to be useful in an intensive care context. Whilst this study demonstrated that the ACIF and IMS correlate strongly across the spectrum of physical function in intensive care patients, there was significant spread of ACIF scores within each IMS category.…”
Section: Discussionmentioning
confidence: 99%
“…The assessor completing the electronic ACIF form also completed an IMS score, an 11-point ordinal scale of function (Hodgson et al, 2014), where a score of 0 indicates function is 'nothing' and 10 indicates 'walking independently without a gait aid'. ACIF and IMS scores were routinely collected electronically for all intensive care patients at least once per week beyond Day 3 of admission, and on intensive care unit discharge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation